2007
DOI: 10.1186/1477-7827-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 9 uterine genes that are regulated during mouse pregnancy and exhibit abnormal levels in the cyclooxygenase-1 knockout mouse

Abstract: Background: Preterm birth is the leading cause of all infant mortality. In 2004, 12.5% of all births were preterm. In order to understand preterm labor, we must first understand normal labor. Since many of the myometrial changes that occur during pregnancy are similar in mice and humans and mouse gestation is short, we have studied the uterine genes that change in the mouse during pregnancy. Here, we used microarray analysis to identify uterine genes in the gravid mouse that are differentially regulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Tnfrsf9 expression increases dramatically in the murine uterus during implantation but decreases between days 13 and 19 of gestation (Zhao et al. ; Eckstrum and Bany ). This downregulation may help maintain a successful pregnancy (Sykes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tnfrsf9 expression increases dramatically in the murine uterus during implantation but decreases between days 13 and 19 of gestation (Zhao et al. ; Eckstrum and Bany ). This downregulation may help maintain a successful pregnancy (Sykes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Zhao, et al showed that Tnfrsf9 mRNA can be detected in the implantation sites of pregnant mice and levels decrease between Days 13.5 and 18 of pregnancy (Zhao, Koon, Curtis, Soper and Bethin, 2007). The present study extends this work and shows that Tnfrsf9 expression dramatically increases in implantation sites of the uterus during the implantation phase of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, although TNFRSF9 seems to play many roles in the immune system, very little is known about Tnfrsf9 expression at implantation sites in the uteri of pregnant mammals. Recently, Tnfrsf9 expression in the late mouse uterus and placenta was partially characterized (Zhao, et al, 2007). However, to the best of our knowledge, little is known about the expression of this gene in the uterus or conceptus during the implantation phase of early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…After ovariectomy, these mice delivered normally, suggesting that, in this species, PGF 2␣ was essential for luteolysis but not for the subsequent process of parturition itself. Ablation of PGHS-1 also causes prolonged gestation, suggesting this isoform was responsible for the endometrial synthesis of the luteolytic PGF 2␣ (95,232). Remarkably, when both the PGHS-1 and OT genes were disrupted, parturition began on time (95).…”
Section: Limitations and Benefits Of Currently Favored Animal Modelsmentioning
confidence: 99%